Anthropometry Based Growth and Body Composition in Infants with Complex Congenital Heart Disease. (June 2022) - Irving, Sharon Y.; Ravishankar, Chitra; Miller, Mary; Chittams, Jesse; Stallings, Virginia; Medoff-Cooper, Barbara
Background: Infants with congenital heart disease (CHD) often have poor growth and altered body composition (fat and muscle accretion). Aim: Describe growth patterns in infants with CHD using interval weight, length, head circumference (HC), triceps (TSF), subscapular skinfolds (SSSF), and mid-upper arm circumference (MUAC) measurements. Subjects and Methods: A total of 120 infants enrolled: 48% healthy and 58% with CHD (45% single ventricle [SV]; 55% two ventricle [2V] physiology). Weight, length, HC, TSF, SSSF, and MUAC measured at 3-, 6-, 9-, and 12-months of age. Results: CHD infants had lower weight, length, and HC z -scores at 3-, 6-, and 9-months. At 9-months, infants with SV physiology had larger TSF and SSSF z -scores over 2V and healthy infants. Overall MUAC z -scores were smaller at 3- and 6-months in infants with CHD. Conclusison: Infants with CHD have a complex pattern of growth. Longitudinal growth and body composition measurements provide information to better understand this pattern.